Review of seizure disorders in children in the age group of six months to five years - Koli, Chandrashekhar; Darne, Sachin (International Journal of Contemporary Pediatrics, 2018)
Background: Seizure disorder a term used to include epilepsy, febrile seizures and other types. The international classification and Diagnostic tools including EEG monitoring and MRI are helpful to categorize seizure and treat them with various antiepileptic medications. Methods: Data from patients in the age group of 6 months to 5 years, over 2 months period, presenting with seizure disorders was collected in prescribed proforma and evaluated for type of seizure disorder, age of onset, family history of seizures, previous history of febrile convulsions, presence of neurological abnormality, EEG changes and response to drugs. They were followed up over a period of 2 years. Results: In this study 200 children’s with seizure disorders from a period of 2 months, were screened, reviewed and followed up for a period of two years. Incidence of seizure disorder is 4.37% with male predominance. Of which febrile seizures (52.5%), Generalized Seizures (25.5%), partial seizures (12%), besides unclassified (10%) and status epilepticus (10%). 12% of the children had positive family history of epilepsy and 14.56% had history of previous febrile convulsion. Birth injuries (19.4%) and CNS infection (38.6%) and space occupying lesions (9.7%) constitute the major etiological factors. 10% patient with seizure disorder had abnormal neurological signs. EEG Examination showed 56.8% normal and 33.2% Generalized abnormality. On follow up 51% where found regular, out of which 30% went into remission. Conclusions: Seizure disorder is quite significant condition in children. Though benign, the febrile seizures are the most common type of seizure in children. The major preventable etiological factors for seizures are Birth trauma and CNS infections. Clinical and EEG work up is necessary for proper management of seizures. Health education is needed to stress the importance of regular treatment and to educate for removal of stigmata.